Factors Affecting The Survival Of Hd Patients With COVID-19 - Gazaly, M. Feldi; Pasaribu, Indah Septiani (Poltekkes Kemenkes Kendari, 2023)
Maintenance hemodialysis (HD) patients experience an increased risk of exposure to COVID-19 and complications of COVID-19 due to comorbidity conditions and the obligation to routine hemodialysis. Patients undergoing HD with end-stage kidney disease (ESRD) are particularly susceptible to SARS-CoV-2 infection and have a high mortality rate. This study aims to assess the correlation of ffactor actors that affect theurvival of HD patients with COVID-19. The design of this study is analytical research with a cross-sectional study retrospective approach. The study was conducted from August to December 2021 at the Medical Record Installation of USU Hospital Medan. The subjects of this study were all regular HD patients at USU Hospital Medan. To assess the relationship of the correlation f factor actors that influence the urvival of HD patients with COVID-19, the Pearson correlation test is used and if the data is not normally distributed, then the test used is the Spearman correlation test. The results of the analysis are said to be significant when p<0.05, with a degree of confidence of 95%. Pearson's correlation values for Hb and platelets with mortality were -0.282 and -0.285 but with p-values above 0.05 so the results were insignificant. The pearson correlation value for albumin with mortality is -0.462 with a p value of 0.013 which means that the test results are significant. Spearman's correlation values for leukocytes and D-Dimer with mortality were 0.296 and 0.307 but with a p-value above 0.05 so the results were insignificant. Spearman's correlation value for CRP with mortality is 0.383 with a p value of 0.044 which means the test results are significant. Albumin levels showed a significant correlation with mortality of HD patients with COVID-19. Meanwhile, CRP levels showed a significant positive correlation with mortality of HD patients with COVID-19.